PENGARUH KUALITAS DAN PROMOSI WEBSITE TERHADAP SIKAP USER SERTA IMPLIKASINYA KEPADA KEPUTUSAN PENGGUNAAN WEBSITE PORTAL (STUDI KASUS WEBSITE PORTAL USEETV.COM) - Novika Erdini; Wilhelmus Harry Susilo (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract. UseeTV is an entertainment portal website. There is no increasing number ofvisitor in page view since 2013 to Q2 2014, although it has been carried out variouspromotional activities. This study aims to examine and analyze the effect of Website Qualityand Promotion of the attitude and consumer decision using UseeTV.com. The research data isthe data page view UseeTV.com starting from 2013-2014. Convenience sampling was use assampling method taken by 402 population UseeTV.com users. Based on that population andusing slovin formulas with the margin error 10% then obtained a sample of respondents asmany as 200 people. Structural Equation Model (SEM) is used for method of analysis study.Research results show that the Website Quality and Promotions significantly affect theAttitude and Consumer Decision. Website Quality is the biggest significant variable ininfluencing attitude and consumers decision to use the portal website UseeTV.com.Keywords : Website Quality, Promotion, Attitude, Consumer Decision